Pengaruh Kebiasaan Berbagi Konten Dakwah di Medsos terhadap Tingkat Resiliensi Akademik pada Mahasiswa Komunikasi dan Penyiaran Islam Generasi Z - Addien, Az-Zahra Kurnia; Muhammad N Abdurrazaq; Alfi Satria (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
Higher education in the digital era requires Generation Z students not only to excel academically but also to develop resilience in coping with various academic pressures. At the same time, the habit of sharing Islamic content on social media serves not only as a means of disseminating religious values but also as a potential factor in strengthening students’ academic endurance. This study aims to analyze the influence of digital da’wah content-sharing habits on the academic resilience of students in the Islamic Communication and Broadcasting (KPI) program. The research employed a quantitative approach using simple linear regression and descriptive analysis based on questionnaire data. The findings indicate that most students demonstrated a moderate level of academic resilience (83%), while their digital da’wah content-sharing habits were also in the moderate category (75%). Regression analysis revealed a significant influence of content-sharing habits on academic resilience, with a coefficient of determination (R²) of 0.459. These results highlight that digital da’wah functions not only as a medium for spreading Islamic values but also as a contributing factor in enhancing the academic resilience of Generation Z students.